Neuronal antibodies in patients with suspected or confirmed sporadic Creutzfeldt-Jakob disease - Rossi, Meghan (J Neurol Neurosurg Psychiatry, 2015)
OBJECTIVES: There have been reports of patients with antibodies to neuronal antigens misdiagnosed as sporadic Creutzfeldt-Jakob disease (sCJD). Conversely, low levels of antibodies to neuronal proteins have been reported in patients with sCJD. However, the frequency of misdiagnoses, or of antibodies in patients with subsequently confirmed sCJD, is not clear. METHODS: We reviewed 256 consecutive cases of sCJD seen in the National Prion Clinic, of whom 150 had sera previously referred for selected antibody tests. Eighty-two available samples were retested for antibodies to N-methyl-d-aspartate receptor (NMDAR), the glycine receptor (GlyR), voltage-gated potassium channel (VGKC)-complex and the associated proteins, leucine-rich glioma inactivated 1 (LGI1) and contactin-associated protein 2 (CASPR2). RESULTS: Four of the initial 150 sera referred were positive; two had antibodies to NMDAR, and two to the VGKC-complex, one of which was also positive for GlyR antibodies. Of the 82 sCJD sera retested, one had VGKC-complex antibodies confirming the previous result, two had CASPR2 and GlyR antibodies and one had CASPR2 and NMDAR antibodies; all antibodies were at low levels. Over the same period three patients with autoimmune encephalitis and high VGKC-complex antibodies were initially referred as sCJD. CONCLUSIONS: This study indicates that <5% patients with sCJD develop serum antibodies to these neuronal antigens and, when positive, only at low titres. By contrast, three patients referred with possible prion disease had a clinical picture in keeping with autoimmune encephalitis and very high VGKC-complex/LGI1 antibodies. Low titres of neuronal antibodies occur only rarely in suspected patients with sCJD and when present should be interpreted with caution.